Barium isotopic fractionation during strong weathering of basalt in a tropical climate. (October 2020) - Gong, Yingzeng; Zeng, Zhen; Cheng, Wenhan; Lu, Ying; Zhang, Lili; Yu, Huimin; Huang, Fang
Graphical abstract: Highlights: Ba isotopic composition is a robust tracer of Ba in soils. Ba is mainly retained by adsorbed on clay minerals and Fe–Mn (oxyhydr)oxides in soils. Light Ba isotopes prefer to be adsorbed on clay minerals and Fe–Mn (oxyhydr)oxides. Heavy Ba isotopes are prone to being released from interlayers of micaceous layers. Light Ba isotopes prefer fluid during silicate minerals dissolution. Abstract: Barium (Ba) is an element which is toxic to humans, plants, and animals. Deciphering the geochemical behavior of Ba in soils is fundamental for assessing the potentials risks posed by Ba. Ba isotopes are a potentially robust tracer of Ba in soils. In this study, the controlling factors of Ba isotopic fractionation in a latosol profile were investigated through sequential-extraction experiments. Furthermore, dissolution experiments were conducted to understand Ba isotopic fractionation during the dissolution of basalts. The sequential-extraction experiments revealed δ 137/134 Ba ratios in various fractions that were remarkably heterogeneous: −0.28‰ to −0.15‰ in the exchangeable fraction; −0.32‰ to −0.16‰ in reducible Fe-Mn (oxyhydr)oxides; and 0.06‰ to 0.46‰ in residues. This indicates that light Ba isotopes are preferentially adsorbed on secondary minerals and associated with Fe-Mn (oxyhydr)oxides. Both processes play important roles in storing Ba originally released from minerals. Results of the sequential-extraction and dissolution experiments revealed that light Ba isotopes favored fluids during the dissolution of silicate minerals, while heavy Ba isotopes were prone to being released from interlayers of micaceous layers. Collectively, the dissolution of minerals, adsorption on secondary minerals, and formation of easily reducible Fe-Mn (oxyhydr)oxides govern Ba isotope fractionation and Ba transport in soils.